ANALISIS TATA KELOLA PEMERINTAH TERHADAP KEMISKINAN - Rizqi, Intan; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Good governance for public services and government that delegate some of its function through decentralization is reflected in the welfare of its citizens. Using path analysis with the variable of economic growth, this study finds that the good governance performed by the government reflected from the local government’s score in the Local Government’s Administration Report (LPPD) does not reduce poverty in 32 Indonesian provinces. This finding supports the research of Kwon dan Kim (2014) that good governance is not significant for poverty reduction and that direct policies related to poverty is required, not through indirect instrument such as good governance. Furthermore, fiscal decentralization from income side reduces poverty because the budget has been allocated to productive expenditures such as poverty eradication programs. In addition, this study also finds that economic growth mediates the effects of public governance and decentralization on poverty.